2019
DOI: 10.1111/jocs.14369
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment results of secondary tunnel‐like subaortic stenosis after congenital heart disease operations: A 7‐year, single‐center experience in 25 patients

Abstract: Objective: To summarize the surgical results of secondary tunnel-like subaortic stenosis (STSS) after congenital heart disease (CHD) operations, the pathogenesis of STSS is analyzed and its operative effect and prognosis are evaluated. Methods: We analyzed clinical data from 25 patients who underwent surgical repair for STSS in Fuwai Hospital from 1 January 2009 to 31 December 2015. There were 17 males and 8 females. The types of CHD included a double outlet right ventricle (DORV), a ventricular septal defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Also, left ventricular remodeling is known to be associated with poor prognosis after surgery [6]. Surgical therapy for SAS consists of correction of the obstruction, which may involve simple membrane removal, extensive ring resection with or without myectomy, or a Konno procedure [7][8][9]. The timing of the surgery varies, with recommendations ranging from early operation to longer periods of observation depending on the patient's characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, left ventricular remodeling is known to be associated with poor prognosis after surgery [6]. Surgical therapy for SAS consists of correction of the obstruction, which may involve simple membrane removal, extensive ring resection with or without myectomy, or a Konno procedure [7][8][9]. The timing of the surgery varies, with recommendations ranging from early operation to longer periods of observation depending on the patient's characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…For the DORV, the decrease in the effective VSD size, turbulent flow, and the sinuous shape of the tunnelization caused subaortic septal or conal muscle hypertrophy or fibrous tissue deposits. 16 Under this circumstance, extended septoplasty was a safe and effective method for the treatment of SAS as Fibro-Muscular Resection. 17 Aortic regurgitation, as the most dreaded sequelae of SAS, appears to be at increased risk, and was also the main risk of reoperation 18,19 This study showed that 61 (93.8%) patients had tri-leaflet valves, and 34 (51.5%) patients had aortic regurgitation before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that one patient with DORV underwent extended septoplasty. For the DORV, the decrease in the effective VSD size, turbulent flow, and the sinuous shape of the tunnelization caused subaortic septal or conal muscle hypertrophy or fibrous tissue deposits 16 . Under this circumstance, extended septoplasty was a safe and effective method for the treatment of SAS as Fibro‐Muscular Resection 17 …”
Section: Discussionmentioning
confidence: 99%
“…SSS also is an iatrogenic disease after biventricular repair of DORV. SSS after biventricular repair of DORV may develop in 3.5-5.5% of cases [Zhang 2020]. The changes in geometric morphology, such as the decrease in the effective VSD size, turbulent flow, and the sinuous shape of the tunnelization, caused subaortic septal or conal muscle hypertrophy or fibrous tissue deposits [Zhang 2020; Kim 2010].…”
Section: E111mentioning
confidence: 99%
“…SSS after biventricular repair of DORV may develop in 3.5-5.5% of cases [Zhang 2020]. The changes in geometric morphology, such as the decrease in the effective VSD size, turbulent flow, and the sinuous shape of the tunnelization, caused subaortic septal or conal muscle hypertrophy or fibrous tissue deposits [Zhang 2020; Kim 2010]. The turning radius of the intraventricular tunnel is the main factor, affecting the pressure difference.…”
Section: E111mentioning
confidence: 99%